Facial antibioma formation: A Case Report - Haydar Mahdey; Danish Muzaffar; Muhammad Sohail Zafar; Muhammad Safwan Malik (Universidad de Concepción., 2018)
Odontogenic infections are associated with a variety of microorganisms. Antibiotics are commonly used for the management of various dental infections and have a proven role in decreasing morbidity and mortality caused by infectious diseases. The frequent and over usage of antibiotics has been associated with a number of consequences such as the selection of drug resistant strains, and the formation of antibiomas. Antibiomas are characterized by the formation of a localized pathology surrounded by thick fibrous tissues in response to long term antibiotics use. An established antibioma is characterized by a tough fibrous swelling accompanied by painful or painless swelling, intermittent fever and constitutional symptoms. In this article, we are reporting the case of a facial antibioma formed due to prolonged use of antibiotics prescribed for a residual periapical infection following endodontic treatment. In addition, the association of using antibiotics in this context is discussed.